Escolarização de aluno com síndrome de Down na escola : um estudo de caso - Marques, Aline Nathalia (2016)
Currently the Down syndrome challenge the school and educators to outline new methodologies and pedagogical practices. Consequently, the teacher is an important mediator to conception internalization, which will be acquired. This way, the objective of this study was analyze written language of a down syndrome’s student in the inclusive classroom context. In addition, as specifics objectives: a) observe the teaching strategies used by the teacher of regular classroom to teach the reading and writing and b) analyze the writing production of the Down syndrome’s student. In this direction, the present study it is qualitative and it is guided in a case study, had as reference the historical-cultural theoretical approach and the dates were collected in a regular classroom second grade in the elementary school. The instruments used were a semi-structured interview and a semi structured used with the teacher of the classroom, participant observation and photographs of the school production of student during the classes. The results has showed an initial and continue training need for teacher who have in their classrooms students with Down syndrome, and with it, thinking with new strategies, because, as was evidence in this research the literacy activities for those students are guided for repetition and memorization techniques. In addition, few different activities were developed with the student been a lagged literacy processes. The written production of the student analyzed, indicated that despite not be literate, the participant student started to attribute signification for your draws, that it is a step for written language acquisition.